Financial Sector and Bilateral Surveillance : Toward Further Integration. (Policy Papers; Policy Paper ;, 2009)
The Fund has continued to make great efforts to enhance financial sector focus and analytics in bilateral surveillance. The main initiatives include enhancing collaboration with other multilateral institutions, improving analytical tools and methodologies, and a major strengthening of the financial sector capabilities in area departments. The fruits of these efforts are already visible in the better treatment of financial sector issues in Article IV reports.